FEATURES OF CONTROL OF THE ELECTRIC DRIVES WITH INDIRECT SPEED MEASURING - Chepkunov, R. A.; Levinzon, D. I. (Radio Electronics, Computer Science, Control, 2013)
The features of control of the electric drives with the indirect measuring of speed are related by the presence of positive feed-back on a current, by the large pulsations of signal of feed-back on voltage in the direct-current electric drive, by the display of instability of electric motor in an asynchronous electric drive. The areas of stability at a positive feed-back on a current in the direct-current electric drive and on the active constituent of current in an asynchronous electric drive are certain. For reduction of the sensor inertness of the thyristor converter voltage the digital smoothing out of pulsations of the feed-back signal offers and the areas of stability of the control system are certain. The areas of stability of asynchronous electric drive are certain depending on the coefficient of dispersion of magnetic stream, electromechanics permanent to time, permanent to time of stator and rotor, the method of suppression of self-excited oscillations offers. The structural schemes and system parameters that ensure quality control are substantiated.